1998
DOI: 10.1046/j.1523-1747.1998.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Activating c-kit Mutations in Adult-, but not in Childhood-Onset Indolent Mastocytosis: A Possible Explanation for Divergent Clinical Behavior

Abstract: Mastocytosis represents a mast cell proliferative disease that generally runs a benign clinical course, with spontaneous remissions mostly by puberty in childhood-onset disease, although rare forms, particularly in adult-onset disease, can be associated with (pre)malignant hematologic disorders and very rarely present as mast cell leukemia or malignant mastocytosis. Reasons for this divergent clinical behavior of childhood- versus adult-onset disease are unknown. Recently, two activating mutations in the intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
156
1
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(167 citation statements)
references
References 34 publications
5
156
1
5
Order By: Relevance
“…Therefore, it is plausible that MEK activation possibly occurs through a c-kit signaling pathway in HMC-1 cells, which synergistically up-regulates TGF-␤-induced TIM-3 transcription. Pathologically, the same c-kit mutations found in HMC-1 are observed in patients with mastocytosis (Buttner et al, 1998;Longley et al, 1999). Furthermore, elevation of the expression levels of SCF and TGF-␤ is observed in human synovium of rheumatoid arthritis as well as in a scleroderma mouse model, of which a common feature is mast cell hyperplasia (Olsson et al, 2001;Wang et al, 2005).…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, it is plausible that MEK activation possibly occurs through a c-kit signaling pathway in HMC-1 cells, which synergistically up-regulates TGF-␤-induced TIM-3 transcription. Pathologically, the same c-kit mutations found in HMC-1 are observed in patients with mastocytosis (Buttner et al, 1998;Longley et al, 1999). Furthermore, elevation of the expression levels of SCF and TGF-␤ is observed in human synovium of rheumatoid arthritis as well as in a scleroderma mouse model, of which a common feature is mast cell hyperplasia (Olsson et al, 2001;Wang et al, 2005).…”
Section: Discussionmentioning
confidence: 74%
“…7 Written, informed consent was obtained from all patients and controls before biopsies were performed. The study was approved by the ethical committee of the Humboldt University, Berlin, Germany.…”
Section: Patients and Tissue Samplesmentioning
confidence: 99%
“…Other less common (<5%) somatic KIT mutations identified in adult SM include V560G [30,31], D815K [32], D816Y [29,[32][33][34], insVI815-816 [29], D816F [32,34], D816H [35], and D820G [36]. Recent studies have confirmed that childhood-onset mastocytosis is also clearly clonal in nature, and is associated with germline or acquired activating KIT mutations [37][38][39].…”
mentioning
confidence: 99%